Когда стихи дружат с картинками : С. Маршак и В. Лебедев: сборник / Н. И. Шантыко - Шантыко Нина Ивановна (Малыш, 1983)
Экземпляры: аб. ДБ (20210622) / Инвентарный номер: 11189 / Сис.шифр: 85.1 / Авт.знак: Ш 22 / ББК: 85.153(2)